Export Marketing in Bangladesh:Problems and Prospects - Alam, Sayeed; Mahmood, Monowar Hossain (Indian Journal of Marketing, 2009)
Exports from developing countries has increased substantially in recent years. Bangladesh, as a developing country, also tried to access to international markets through following the export marketing strategies. However, business organizations in Bangladesh are facing dearth of knowledge about export marketing problems and remedies in this regard. The present study tried to accumulate the existing scattered information and literature to provide some guidelines for the export marketers and the policy makers. Future research incorporating on more empirical data and facts were suggested for helping the business organizations to improve the export performance of in Bangladesh.